Reasons As Evidence Against Ought-Nots. (1st September 2020) - Lee, Kok Yong
Abstract: Reasons evidentialism is the view that normative reasons can be analyzed in terms of evidence about oughts (i.e., propositions concerning whether or not S ought to Φ). In this paper, I defend a new reason-evidentialist account according to which normative reasons are evidence against propositions of the form S ought not to Φ. The arguments for my view have two strands. First of all, I argue that my view can account for three difficulty cases, cases where (i) a fact is both a reason for S to Φ and a reason for S not to Φ, (ii) a fact is both evidence for the proposition that S ought to Φ and evidence for the proposition that S ought not to Φ, and (iii) the subject is genuinely torn, as far as reasons are concerned, between Φ-ing and not Φ-ing. Second, I argue that my view can account for what a reason against S Φ-ing is.